2016
DOI: 10.1111/1471-0528.14265
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated leiomyoma cells can be identified following conventional myomectomy

Abstract: Even during conventional myomectomy, tissue spillage occurs during resection of leiomyoma(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Vargas et al compared outcomes of women who underwent open versus contained morcellation and the only difference was an increase in operating time (69). Some argue that myometrial spillage occurs during the process of myomectomy and that spillage of myometrial cells has been noted even after open myomectomy (70). Others suggest that thorough irrigation after the use of power morcellation will negate the need to use a bag (71) and even when bags are used, myometrial cells can still be found within the abdomen (72).…”
Section: Alternatives To Power Morcellationmentioning
confidence: 99%
“…Vargas et al compared outcomes of women who underwent open versus contained morcellation and the only difference was an increase in operating time (69). Some argue that myometrial spillage occurs during the process of myomectomy and that spillage of myometrial cells has been noted even after open myomectomy (70). Others suggest that thorough irrigation after the use of power morcellation will negate the need to use a bag (71) and even when bags are used, myometrial cells can still be found within the abdomen (72).…”
Section: Alternatives To Power Morcellationmentioning
confidence: 99%
“…Therefore, we can only strive to develop innovative strategies aimed at reducing the theoretical risks. Indeed, it should also be borne in mind that the dissemination of specimen debris can occur during the myomectomy (enucleation) phase of the procedure, and even in cases of open surgery and intact specimen extirpation, there may be uterine tissue disruption and fluid spread . The search for safe alternatives to the use of intracorporeal electromechanical morcellation is, however, critical to avoid the well‐described, more commonly occurring risks of traditional laparotomy with increased morbidity and mortality .…”
Section: Discussionmentioning
confidence: 99%
“…However, enucleating leiomyomas per se may be inappropriate from an oncological perspective because complete, radical resection of malignant tumors to prevent further tumor growth or recurrence is not achieved. The aim of a study from the Netherlands was to determine whether spillage of leiomyoma cells occurs during open myomectomy [18]. Women undergoing open myomectomy were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue spillage from leiomyoma(s) occurs during conventional open myomectomy. The clinical relevance of tissue dissemination after myomectomy is unclear, but it cannot be excluded that this may negatively affect the patient's outcome if there is malignant change within the enucleated leiomyoma(s) [18]. Here, the authors questioned whether morcellation in specially designed containment bags after laparoscopic myomectomy guarantees any additional oncological safety [18].…”
Section: Discussionmentioning
confidence: 99%